The Effect of Compensation, Transformational Leadership and Organizational Culture on Employee Turnover Intensity - Ringkot Sihotang (IJHCM (International Journal of Human Capital Management), 2021)
Background - PT. Lestari Banten Energi is a subsidiary under Genting Group and is engaged in the electricity industry. Based on the phenomenon that occurred at PT. Lestari Banten Energi that employee turnover is very high so that employee turnover can affect the company's operational activities. In addition, employee turnover can also affect work culture due to differences in individual thinking. Purposed - This study aims to determine the effect of compensation on the intensity of employee turnover, transformational leadership style on the intensity of employee turnover and to see the effect of organizational culture on the intensity of employee turnover. Originality /Value - The novelty in this study is that there is no research on compensation, transformational leadership and organizational culture on the intensity of employee turnover at PT. Lestari Banten Energi. Research Limitations - information, primary and secondary data in this study were only obtained from PT. Lestari Banten Energy. Design/methodology/approach - The population and sample of this study were employees of operation and maintenance at PT. Lestari Banten Energi numbered 42 people. This study uses a quantitative approach method. The data collection technique used primary data in the form of a questionnaire. The data analysis technique of this research uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. Findings - This study shows that 1) Compensation has a negative and insignificant effect on turnover intensity, 2) Transformational leadership has a negative and insignificant effect on turnover intensity, 3) Organizational culture has a negative and insignificant effect on turnover intensity.